Implications of the Sociology of Religion of Carl Gustav Jung's Theory of Individuation: The Role of Pancasila and Local Wisdom in Responding to the Challenges of Postmodern Society - Ivan Th. J. Weismann; Johana Betris Tumbol; Randy Frank Rouw; Hengki Wijaya (Pharos Journal of Theology)
Postmodern society faces challenges such as collective aggression and value fragmentation. Carl Gustav Jung’s theory of individuation, which emphasizes self-integration through archetypes (collective unconscious images), is relevant for examination through the lens of the sociology of religion to understand potential solutions to these issues. This study aims to analyze the sociological implications of Jung’s individuation theory in the context of postmodern societal problems, particularly the role of Pancasila and local wisdom as archetypes of self-development. The research employs a literature review method with a qualitative-interpretative approach, analyzing the works of Jung, Pancasila, and Javanese local wisdom (Rasajati). Pancasila functions as an active archetype and "dialogical partner" in national development—offering correction, guidance, and peace. The collective transformation of Pancasila values in national life can reduce mass aggression. Rasajati (Javanese local wisdom) represents existential embodiment through the practice of laku (reasoning–decision–action), guiding individuals to achieve Kasunyatan (ultimate reality) and cosmic consciousness—similar to Jung’s concept of individuation. Pancasila and local wisdom are not merely ideologies or traditions but also serve as collective archetypes. Both are capable of mediating conflict, integrating the self, and restoring social cohesion amidst the complexities of postmodern society.